Sumbangan Pemikiran Filsafat Pendidikan Paulo Freire Bagi Sistem Pendidikan Tinggi Indonesia - Damianus Pongoh; Harol R. Lumapow; Jeffry S. J. Lengkong; Viktory N. J. Rotty; Ignatius J. C. Tuerah (Media (Jurnal Filsafat dan Teologi), 2022)
This essay discusses the philosophy of education according to Paulo Freire, specifically methodology in the education process. The main question deals with the contribution of Freire's thought to the education system in Indonesia. Through literature review, the author underlines the concept of education as a process of liberation. Education is no longer regarded as a transfer of knowledge, but a process of change to create social structures that are more just and humane. Freire criticizes the bank-style education model which makes the teacher the subject, while the student as an object like an empty box to be filled. According to Freire, education should be developed as problem-posing education, namely education that aims at posing and discussing actual problems. It can be the main inspiration for the education system in Indonesia. This approach allows students to freely and creatively recognize their abilities and the reality of the problem objectively-contextually and respond appropriately to problems by creating productive and changing-oriented works.